Determinants and outcome of early marriage among adolescents: A descriptive study - Rajan Naroor, Beena; Tribhuwan, Robin D. (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The present study was aimed to study different social, obstetric, and antenatal characteristics in adolescent married girls and compared them with primigravida women. Subjects & methods: The descriptive study was conducted among lactating adolescent mothers within the age group of 15-24 years residing in Pimpri Chinchwad Municipal Corporation (PCMC) slums. The subjects were mothers and should have children below 24 months for adolescent girls and primigravida (a mother with a living child 0-24 months). Results: The proportions of younger women [i.e. 15 – 19 years] were significantly more among adolescent marriage girls as compared to primigravida women [2.4% vs 40.0%, p < 0.0001]. However, thought not statistically significant, the proportion of less educated [up to primary level] [11.8% vs 25.9%, p = 0.135], labourer/construction labourer [10.6% vs 23.5%, p = 0.164], SC / ST women [28.3% vs 29.5%, p = 0.874], OBC women [25.9% vs 30.6%, p = 0.874], Buddhist [11.8% vs 15.3%, p = 0.631] and living in a joint family [43.5% vs 49.4%, p = 0.723] were more among adolescent married girls as compared to primigravida women. Surprisingly, high duration of stay in urban place i.e. Pune city [35.3% vs 44.7%, p = 0.32] was more among the adolescent married girls as compared to primigravida women. The association of status of receiving antenatal services [ANS] during the pregnancy was not statistically associated with age at the first pregnancy [study/control group] [91.8% vs 82.4%, p = 0.152]; but provides mathematical relationship of less proportion among adolescent married girls as compared to primigravida women. Conclusion: Our study found important determinants of adolescent marriage including education, poverty, social pressure etc, which ultimately determine pre-natal and perinatal characteristics.